Pro-social content in popular animated cartoons viewed by Egyptian children - Nada, Lina (AUC Knowledge Fountain, 2016)
Social Cognitive Theory posits that children can learn from observations specially if repeated, directly or indirectly reinforced, and the audience feels competent in doing them. While much of the focus of research was on the negative aspects or the antisocial content specially in the Arab region, the present study studies prosocial content. Prosocial behaviors is a socially desirable intended behavior that in some way benefits another person or society at large. A content analysis was used to examine the content of the popular cartoons of children aged 7-12 years old who based on research are able to comprehend the messages conveyed in cartoons. The study examined 87 cartoons that were shown during prime time on the three free networks that target that age which are: Cartoon Network Arabia, Spacetoon Arabic and MBC3. A total of around 42 hours was studied. The findings showed that children are exposed to around 10 acts of prosocial behavior every hour they watch television. More than half of the prosocial behavior was classified as physical behaviors. Altruism was the most common prosocial behavior portrayed, followed by positive interaction. The main motive for the prosocial behavior was clear need which was present in 249 of the acts out of 443, followed by altruistic motivation then, demonstration of friendship. Approximately 75% of prosocial acts were conducted by male characters mostly adults and teenagers. Overall, there were more prosocial acts by high social economic status characters 46.5% as compared to middle (34.09%). Most prosocial acts were conducted by average (49.89%) or attractive (41.76%) characters in comparison with unattractive (6.55%). Most of the prosocial acts were between friends (46.05%) followed by family. Most of the acts had a low cost to the initiator; were rewarded; there was a clear need and it was done with pure intentions. The different elements of the theory were present in the results which makes the probability of children learning positive behaviors very high.